2011
DOI: 10.1208/s12249-011-9713-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Optimization of Orodispersible Mosapride Film Formulations

Abstract: Orodispersible film (ODF) technology offers new possibilities for drug delivery by providing the advantages of oral delivery coupled with the enhanced onset of action and convenience to special patient categories such as pediatrics and geriatrics. In this study, mosapride (MOS) was formulated in an ODF preparation that can be used for treatment of patients who suffer from gastrointestinal disorders, especially difficulty in swallowing due to gastroesophageal reflux disease. Poloxamer 188 was used to solubilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 19 publications
5
57
0
Order By: Relevance
“…Rabek et al (2014) also found that increasing triethyl citrate concentration decreased the TS of the investigated films prepared using cellulose acetate phthalate and Pluronic F-127 combined together (70:30 w/w). These results are also in accordance with the results obtained by ElMeshad & El Hagrasy (2011) in their study on the preparation of mosapride orodispersible films. Their results demonstrated that using 15% plasticizer resulted in significantly higher film stiffness as can be seen from the higher TS values compared to films containing 20 and 25% plasticizer.…”
Section: Tensile Strengthsupporting
confidence: 92%
“…Rabek et al (2014) also found that increasing triethyl citrate concentration decreased the TS of the investigated films prepared using cellulose acetate phthalate and Pluronic F-127 combined together (70:30 w/w). These results are also in accordance with the results obtained by ElMeshad & El Hagrasy (2011) in their study on the preparation of mosapride orodispersible films. Their results demonstrated that using 15% plasticizer resulted in significantly higher film stiffness as can be seen from the higher TS values compared to films containing 20 and 25% plasticizer.…”
Section: Tensile Strengthsupporting
confidence: 92%
“…Colloidal formulations have also been shown to enhance transdermal skin penetration. [54][55][56] Results presented here demonstrate that delivery of macromolecules can be effectively achieved without the use of any specific delivery devices or the need to design complex formulations.…”
Section: Discussionmentioning
confidence: 80%
“…In vitro disintegration time of all the formulations was analyzed by adopting visual method [14, 15]. Film strip was placed in a Petri dish (internal diameter 5 cm) containing 10 mL of PBS at 37°C.…”
Section: Methodsmentioning
confidence: 99%